2023
DOI: 10.1002/advs.202301312
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Co‐Enhancement of Remanence–Coercivity of RE‐Fe‐B Sintered Magnets with High Ce‐Content: Appropriate La Substitution

Abstract: The development of low-cost RE-Fe-B sintered magnets with large La/Ce content is of great significance for the balanced utilization of rare earth (RE) resources, but it is limited by reduced magnetic properties. In this work, the coercivity (H cj ), remanence (B r ), maximum energy product [(BH) max ], and temperature stability are simultaneously enhanced for magnets with LaCe accounting for 40 wt% of the total RE. The synergistic regulation of the REFe 2 phase, Ce-valence, and grain boundaries (GBs) in RE-Fe-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…[21] In addition, as the La content increased, fractions of the rare earth-rich phase and the CeFe 2 phase decreased, strengthening the exchange coupling effect between matrix phase grains. [17] The large segregation area of the β -La phase would generate poor GBs between matrix grains, [4] and they may act as nucleation sites for the reverse magnetization domains and worsen the H cj of ribbons.…”
Section: Effects Of La/ce Ratio On the Microstructure And Magnetic Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…[21] In addition, as the La content increased, fractions of the rare earth-rich phase and the CeFe 2 phase decreased, strengthening the exchange coupling effect between matrix phase grains. [17] The large segregation area of the β -La phase would generate poor GBs between matrix grains, [4] and they may act as nucleation sites for the reverse magnetization domains and worsen the H cj of ribbons.…”
Section: Effects Of La/ce Ratio On the Microstructure And Magnetic Pr...mentioning
confidence: 99%
“…To curb the cost of permanent magnet production, the cost-effective Ce-Fe-B [1][2][3] and (La,Ce)-Fe-B [4][5][6][7][8][9] rare earth permanent magnets have attracted wide attention. Herbst et al [10,11] and Soeda et al [12] reported the hard magnetic properties of Ce 2 Fe 14 B and (La,Ce) 2 Fe 14 B compounds, respectively.…”
Section: Introductionmentioning
confidence: 99%